Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Konsumen Tell Kopi Kediri - Aldi Muflih Azhari (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of service quality variables (X1) and location (X2) on purchasing decisions (Y) at Tell Kopi Kediri. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the research was 267 respondents at Tell Kopi. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y = 16.559 + 0.316 Location has a partially significant effect on purchasing decisions with a sig result of 0.000 <0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that service quality and location simultaneously and significantly influence purchasing decisions.